La Norme Comme Moteur D'itération Qualitative en E-learning: lecture dans le Contexte International et Tunisien - Zghidi, Sihem (جامعة منوبة - المعهد العالي للتوثيق, 2015)
All projects that aim to set standards claim to act as engines for quality and productivity improvement. In the context of e- Learning, standards implementation is especially justified by a quest for interoperability between educational devices and the development of their innovative, autonomous and socialized operating mode. Contrary to popular belief which claims the immobility of standardized objects, standard forms are part of an iterative process requiring at each cycle of its updating a new quest for innovation, creativity and interoperability within diversity. In this article, we start from the different forms of the standard digital version and their application modes to show how the quality of an educational device approach is justified through an iterative and cyclical process of revision and update of technological standards. Some concrete examples will be used to support this hypothesis. These examples are not only taken from the context of Tunisian universities, but they are also examples from the international normative framework which is directly concerned with normative issues in e-Learning (international and European organizations for standardization of distance learning).
يعتبر كل مشروع معياري محركا لتحسين الجودة وتنمية الإنتاجية. في سياق التعلم الإلكتروني، يعتبر تنفيذ المعايير حافز من اجل التوافق بين المنصات التعليمية وتنمية إمكانياتها التشغيلية المبتكرة إبعادها التقنية والمجتمعية. وخلافا للأفكار السائدة حول انغلاق المواد المقننة وجمودها، تندرج صياغة المواصفات بصفة طبيعية في مسار ترديدي يتطلب في كل مرحلة من مراحله سعيا متجددا للابتكار والإبداع والتشغيل البيئي في إطار تعددي ومتنوع. في هذه المقالة، سوف تنطلق من الأشكال المختلفة للمعايير الرقمية وطرق تطبيقها لإظهار كيف يمكن لمسار تقييمي لجودة المنصات التعليمية أن يتحقق من خلال عملية تكرارية ودورية لمراجعة المعايير التكنولوجية وتحديثها. وسوف نستخدم في ذلك أمثلة ملموسة لدعم هذه الفرضية. وهي أمثلة منبثقة على حد سواء من تجربة ذاتية في السياق الجامعي التونسي، وأيضا من المحيط المعياري الدولي المعني مباشرة بالقضايا المعيارية للتعليم عن بعد (منظمات دولية وأوروبية لتقنين التعليم الإلكتروني).
Keywords: الجودة الترديدية -- المواصفات البيداغوجية -- التعليم عن بعد